John Dewey and Henry George: The Socialization of Land as a Prerequisite for a Democratic Public. (11th January 2018) - England, Christopher
Abstract: John Dewey frequently praised Henry George, author of a plan to confiscate land values with a "single tax." Scholars have failed to account for Dewey's support of George. Some have argued that it should not be taken seriously because it is at odds with their interpretation of Dewey's philosophy. This article demonstrates that Dewey perceived the socialization of land values as an essential step toward creating a true democracy. Furthermore, Dewey's interest in George was not an aberration; it was exemplary of his faith in ideology, theory, and transformative social policy. Despite contentions to the contrary, pragmatists of the early 20 th century never emphasized skepticism, moderation, or rote empiricism. In fact, Dewey embraced the philosophy of Henry George as a general theory of history of society. During the Great Depression, Dewey attacked the piecemeal reformism of the New Deal in favor of the comprehensive vision of Henry George.